TUJUAN HUKUM ISLAM DALAM KONTEKS PERLINDUNGAN HAK ASASI MANUSIA DI INDONESIA: KAJIAN MAQASHID AL-SYARI’AH - Nurun Nida Waddiny; Anwar Hafidzi (Makkah: Journal Of Islamic Studies, 2025)
This study explores the intersection between Islamic law and human rights in the context of national law in Indonesia. The main focus of this study is to analyze how the concept of Maqashid al-Syari'ah functions as a theological basis for protecting basic human rights. Using normative legal research methods with a conceptual and philosophical approach, this study examines classical Islamic literature and Indonesian positive legal instruments. The results show significant harmony between the five universal principles of Islam (al-kulliyāt al-khams) and Articles 28A-J of the 1945 Constitution, covering the protection of life, religion, reason, lineage, and property. The practical implementation can be seen in the role of zakat in economic justice and the contribution of the Religious Courts in protecting the rights of women and children. However, challenges in the form of interpretative tensions regarding minority rights are still found in the field. This paper concludes that wise harmonization between Islamic law and national law is crucial to strengthening pluralism and inclusive human rights protection in Indonesia. Kata Kunci: Maqashid al-Syari’ah, Hak Asasi Manusia, Hukum Islam, UUD 1945, Indonesia